O princípio da autonomia patrimonial frente ao exercício da atividade empresarial realizada por uma única pessoa - Moscatini, Áurea (2013)
The thesis examines the strengthening of the Principle of Asset Autonomy in the face of the exploitation of business activity by a single person. It is part of an approach on the general principles of law, involving the search for values, differentiating them from rules and integrating into other principles. It also analyzes single shareholdership in Brazil, with the enactment of Law No. 12.441/11, which focuses on the Individual Limited Liability Company, highlighting its strengths and weaknesses, and particularly demonstrating whether it represents a new kind of society or a new entity altogether, a type of Legal Entity. It presents a historical foreshortening in Brazil, as well as analyzing the experience of Foreign Law on single shareholdership. Lastly, the study points out challenges and perspectives to be overcome for the implementation, enforcement and modification of the legislation on single shareholdership and its harmony within the Principle of Asset Autonomy, demonstrating that there is a connection between the institutions, no longer justifying shareholdership by more than one party in order to ensure Asset Separation